ANALISIS TEKS EDITORIAL DAN OPINI PADA SURAT KABAR KOMPAS.ID - Hasanah, Septia Uswatun; Nisa, Khairun; Hasanah, Uswatun; Nurzafira, Istiqomah (Laboratorium Pembelajaran Bahasa, FKIP Universitas Lampung, 2024)
Newspaper editorials and opinions are types of writing that conduct subjective analysis based on facts and data. Various controversial topics, such as politics, environment, health, economy, and culture, can be found in editorial and opinion texts. Analysis of newspaper editorials and opinions requires an understanding of text structure, facts, and opinions. Editorial and opinion texts must have several characteristics, including being systematic and logical, discussing problems in depth, convincing readers, and containing opinions and facts supported by data or expert opinions. Statements of opinion, arguments, and reaffirmations form the structure of editorial texts. Many journals have studied editorial and opinion texts in newspapers. These journals can certainly be a reference to improve understanding of the analysis of editorial and opinion texts in newspapers. By using a discourse and critical approach, researchers in these journals analyze editorial and opinion texts. In this article, the author will analyze the Editorial and Opinion Texts in the Kompas.id Newspaper. The results of this study can provide a deeper understanding of newspaper opinions and editorial texts. Editorial dan opini surat kabar adalah jenis tulisan yang melakukan analisis subyektif berdasarkan fakta dan data. Berbagai topik kontroversial, seperti politik, lingkungan, kesehatan, ekonomi, dan budaya, dapat ditemukan dalam teks editorial dan opini. Analisis editorial dan opini surat kabar membutuhkan pemahaman tentang struktur teks, fakta, dan pendapat. Teks editorial dan opini harus memiliki beberapa karakteristik, antara lain sistematis dan logis, membahas masalah secara mendalam, meyakinkan pembaca, and mengandung pendapat dan fakta yang didukung oleh data atau pendapat ahli. Pernyataan pendapat, argumentasi, dan penegasan ulang membentuk struktur teks editorial. Sudah banyak jurnal yang meneliti teks editorial dan opini di surat kabar. Jurnal-jurnal terseut tentu dapat menjadi referensi untuk meningkatkan pemahaman tentang analisis teks editorial dan opini di surat kabar. Dengan menggunakan pendekatan wacana dan kritis, para peneliti dalam jurnal-jurnal tersebut menganalisis teks editorial dan opini. Pada artikel ini, penulis akan menganalisis mengenai Teks Editorial dan Opini pada Surat Kabar Kompas.id. Hasil penelitian ini dapat memberikan pemahaman yang lebih dalam tentang opini dan teks editorial surat kabar.